Surface and tribological properties of oxide films on aluminium alloy through fly-ash reinforcement - Mat Tahir, Noor Ayuma; Liza, Shahira; Fukuda, Kanao; Mohamad, Syazwani; Hashimi, Mohd Zakir Fathi; Mohd Yunus, Mohd Saifulnizam; Yaakob, Yazid; Othman, Intan Sharhida (Multidisciplinary Digital Publishing Institute, 2022)
Hard anodizing has proven to be a helpful surface treatment for aluminium alloy and typically accompanied by the growth of a porous and highly flawed oxide layer. The presence of pores on the oxide surface can be taken as an advantage in improving the surface properties. Fly-ash particles are high in SiO2 and Al2O3 content and can be utilized as inexpensive strengthening particles, which can increase the wear resistance and microhardness of composite material. It was noticed that limited research had been carried out in utilizing fly-ash as reinforcement on composite oxide coating as a wear resistance candidate. Thus, this study focused on reinforcing fly-ash on oxide coating and investigating its tribological performance. The composite oxide coating was grown on AA2017 aluminium alloy through anodizing process. To understand the effect of anodizing time and fly-ash content, the parameters were varied from 5–60 min and 0–50 g/L, respectively. The findings suggested that 60 min of anodizing time provides the highest thickness and surface roughness at 35 µm and 6.5 µm, respectively. Interestingly, composite oxide coating with 50 g/L fly-ash provides the highest coating thickness but has the lowest roughness at 52 μm and 8.2 μm, respectively. The composite oxide coatings are observed to reduce friction only for a limited time, despite their potential in significantly reducing the wear rate. The wear mechanism observed was adhesion, micro-crack, and delamination. The findings of this study are believed to provide insight on the potential of fly-ash to be a reinforcement for wear-reduction materials.